2019
DOI: 10.1021/acsomega.9b00336
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Durable Antifog Thin Coatings on Plastic Films by UV-Curing of Proteinoid Prepolymers with PEG-Diacrylate Monomers

Abstract: Fog formation on transparent surfaces constitutes a major challenge in several optical applications, such as plastic packaging, lenses, mirrors, and windshields. To overcome this problem, we prepared and characterized durable antifog thin coatings on plastic films such as polyethylene terephthalate (PET). Proteinoids are biocompatible random polymers made of α-amino acids by thermal step-growth polymerization. Proteinoid prepolymers were prepared by adding activated double bonds to proteinoids via the Michael … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Table 1 exhibits the molecular weights and polydispersity indices (PDIs) of the R d GD, R d GD d , RGD, and RGD d proteinoid polymers. The relative high molecular weights (67,660–69,066 Da) and the very narrow molecular weight monodispersity are not expected but fit to our previous publications 18 , 24 , 25 because common step-growth polymerization processes result in low-molecular-weight polymers with broad molecular weight polydispersity. 26 …”
Section: Results and Discussionsupporting
confidence: 84%
“…Table 1 exhibits the molecular weights and polydispersity indices (PDIs) of the R d GD, R d GD d , RGD, and RGD d proteinoid polymers. The relative high molecular weights (67,660–69,066 Da) and the very narrow molecular weight monodispersity are not expected but fit to our previous publications 18 , 24 , 25 because common step-growth polymerization processes result in low-molecular-weight polymers with broad molecular weight polydispersity. 26 …”
Section: Results and Discussionsupporting
confidence: 84%
“…Table 1 exhibits the molecular weight and polydispersity indices (PDI) of the obtained P(R D GD). The relative high molecular weights (67 660 Da) and very narrow molecular weight monodispersity is not expected but ts to our previous publications, 17,26,27 since commonly step-growth polymerization processes result in low molecular weight polymers with broad molecular weight polydispersity. 28 The P(R D GD) proteinoid was characterized by FTIR spectrometer and UV-Vis spectroscopy.…”
Section: Synthesis and Characterization Of The R D Gd Proteinoidmentioning
confidence: 59%
“…Among the simple methods to prevent fogging of the eyewear, a variety of methods including the application of surfactant liquid, converting the eyewear to a filtered eye mask by creating vents sealed with N95 mask cutting and use of anti-fog glasses or anti-fog coating have been described. 6 , 9 , 12 , 13 However, the actual effectiveness of these methods which perform the operative procedures remains unknown. We tested three inexpensive modifications on a disposable sealed poly-hydrocarbon based protective eyewear and found that the detergent-based liquid surfactant was effective in maintaining the workable vision for as long as 2 h. The PET material based anti-fog film although prevented fogging for long but failed to provide the workable vision required for a simulated surgical task.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Therefore, a low-cost modification of the hermetically sealed protective eyewear that can prevent fogging is desirable in the current times. Plastic films such as polyethylene terephthalate (PET) with surface modifications, 12 surfactant sprays, 6 , 13 and addition of N95 mask cutting to the air vents of the sealed eyewear 9 are some attractive low-cost modifications to prevent fogging of the viewing frames. However, their effectiveness in a real surgical scenario or a simulated operating room environment with the aforestated modified parameters has not been tested.…”
Section: Introductionmentioning
confidence: 99%